Synthesis, Spectral Studies and Anti-Inflammatory Activity of 2-Acetyl Thiophene - B. Ramesh; B. Someswara Rao (E-Journal of Chemistry)
Some new chalcones have been synthesized by the condensation of 2-acetyl thiophene with various aromatic aldehydes in 40% alkali. The synthesized compounds were identified by spectral data and screened for anti-inflammatory activity. Some of these compounds showed moderate to considerable anti-inflammatory activity.